Breakthrough adsorption studies of mixed gases on mango (Mangifera indicaL.) seed shell derived activated carbon extrudes. Issue 4 (December 2015) - Munusamy, Kuppusamy; Somani, Rajesh S.; Bajaj, Hari C.
Abstract: Herein, we report the use of mango seed shells as carbon precursor for producing high surface area (2500 m 2 /g) activated carbon with total pore volume of 2.2 cm 3 /g by chemical (H3 PO4 ) activation method. The mango seed shell derived activated carbon (MSS-AC) was used as adsorbent for the adsorption of CO2, CH4 and N2 . The MSS-AC powder was converted into shaped body (extrudes) using carboxy methyl cellulose sodium salt (viscosity 1% w/v in water at 25 °C, 1100–1900 cPS) and soluble starch (MW: 342.30) as binder (10 wt% of each). The single column breakthrough adsorption of CO2 and CH4 from binary gas mixtures (CO2 –N2, CH4 –N2, CO2 –CH4 ) and ternary gas mixture (CO2 –CH4 –N2 ) were investigated on MSS-AC extrudes. The highest equilibrium adsorption capacity of CO2 on MSS-AC powder obtained was 21.3 wt% and MSS-AC extrudes was 14.3 wt% at 273 K and 1 bar pressure. We have also compared the results of surface area and CO2 adsorption capacity of carbon based materials derived from various sources reported in the literature with MSS-AC.